Boruto : Naruto next generations. Volume 9, Up to you - Kodachi, Ukyo, 1979- (Shonen Jump manga., 2020)
"The battle between Naruto and Delta heats up as Boruto watches on from the sidelines. But when Delta starts using some despicable tactics, the kids may be forced to join the fight. Naruto is strong, but can he fend off such a fearsome foe while protecting others?"--